Moment estimation of customer loss rates from transactional data. (1998) - Daley, D. J.; Servi, L. D.
Abstract : Moment estimators are proposed for the arrival and customer loss rates of a many-server queueing system with a Poisson arrival process with customer loss via balking or reneging. These estimators are based on the lengths { S j 1 } of the initial inter-departure intervals of the busy periods j = 1, …, M observed in a dataset consisting of service starting and finishing times and encompassing both busy and idle periods of the process, and whether those busy periods are of length 1 or > 1 . The estimators are compared with maximum likelihood and parametric model-based estimators found previously.